Contemporary global issues in human resource management - Turkmenoglu, Mehmet Ali, 1986-; Cicek, Berat, 1984- (Emerald Publishing Limited, 2020)
Globalization, digitalization and social changes are rapidly impacting the world of business and in-turn, Human Resource Management practices. The book examines issues that employees encounter in the workplace: ethics, diversity, discrimination, generational differences, conflicts, participation, digitalization and work-life balance. Practitioners and researchers will gain enhanced understanding and awareness of these issues and more as they are investigated through an interdisciplinary, international and critical point of view.
Includes index.
Keywords: Personnel management.; Industrial relations.; Business & Economics -- Human Resources & Personnel Management.; Personnel & human resources management.; elektronické knihy; electronic books